The effects of substrate temperature on refractive index dispersion and optical constants of CdZn(S0.8Se0.2)2 alloy thin films - Ilican, Saliha; Caglar, Yasemin; Caglar, Mujdat; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2009)
The effect of substrate temperature on optical properties of CdZn(S0.8Se0.2)(2) thin films deposited onto glass substrates by the spray pyrolysis method has been investigated. The average optical transmittance of the films was over 74% in the visible range. The optical absorption studies reveal that the transition is direct with band gap energy values between 2.86 and 2.92 eV. The optical constants such as refractive index and dielectric constant of the films were determined. According to variation of the substrate temperature, the important changes in absorption edge, refractive index and the dielectric constant were observed. The refractive index dispersion curves of the films obey the single oscillator model and oscillator parameters changed with substrate temperature. The most significant result of the present study is to indicate that substrate temperature of the film can be used to modify in the optical band gaps and optical constants of CdZn(S0.8Se0.2)(2) thin films. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: CdZnSSe; Optical constants; Single oscillator